In vitro Growth Response of Taraxacum officinale Weber ex F.H. Wigg Regenerated from Different Type of Explants - Ermayanti, Tri Muji; Martin, Andri Fadillah (Annales Bogorienses, 2011)
Dandelion (Taraxacum officinale Weber ex F.H. Wigg) is a medicinal plant species, reported to have some active compounds useful as anti-cancer, anti-inflammatory, antioxidants, and diuretics. Study on in vitro secondary metabolic production and tissue culture of these plants has been reported. This research was aimed to investigate plant regeneration from leaf blade, petiole and root as explants grown in selected media. Three different type of explants were cultured in MS solid medium supplemented with BAP (0, 0.5, and 1.0 mg/l) combined with NAA (0, 0.5, 1.0, and 2.0 mg/l) to select the best medium for spontaneous regeneration. Explants were grown for 6 weeks, the viability of explants, and formation of callus, shoots as well as roots were recorded. The results showed BAP at 1 mg/l combined with at 0.5 mg/l of NAA was suitable for shoot formation, whereas NAA alone was suitable for root formation from leaf blade and petiole. Root was the best explant for shoot regeneration, callus was grown at the first two weeks, and multiple shoots were grown after 3 weeks. No roots were found from root explant. The best medium for multiple shoot regeneration was MS containing 1 mg/l BAP without or with addition of 0.5 mg/l NAA.